

Line 1: 
Line 1: 
−  == It's me meljel lol ==  +  == hi. == 
   
−  <cmath> \begin{align*}
 +  if ur from hysb then bye 
−  ax^2 + bx + c &= 0\\
 
−  a(x^2 + \frac bax + \frac ca) &= 0\\
 
−  a({(x + \frac {b}{2a})}^2  \frac{b^2}{4a^2} + \frac ca) &= 0\\
 
−  {(x + \frac {b}{2a})}^2  \frac{b^2}{4a^2} + \frac ca &= 0\\
 
−  {(x + \frac {b}{2a})}^2 &= \frac{b^2}{4a^2}  \frac ca\\
 
−  {(x + \frac {b}{2a})}^2 &= \frac{b^2}{4a^2}  \frac {4ac}{4a^2}\\
 
−  {(x + \frac {b}{2a})}^2 &= \frac{b^2  4ac}{4a^2}\\
 
−  x + \frac {b}{2a} &= \pm\sqrt{\frac{b^2  4ac}{4a^2}}\\
 
−  x + \frac {b}{2a} &= \pm\frac{\sqrt{b^2  4ac}}{2a}\\
 
−  x &=  \frac {b}{2a} \pm\frac{\sqrt{b^2  4ac}}{2a}\\
 
−  x &= \frac{ b \pm \sqrt{b^2  4ac}}{2a}\\
 
−  \end{align*}
 
−  </cmath>
 
   
 == hihiihi ==   == hihiihi == 